The Utilization of Game-Based Quizizz Application in Learning Education Management for PGMI Students at IAIN Kudus - Uswatun Hasanah; Retno Susilowati; Sabarudin Sabarudin (Al Hikmah: Journal of Education, 2023)
This research was motivated by the utilization of the quizizz application in learning education management to increase student learning interest in the PGMI study program at IAIN Kudus. The purpose of this study was to examine the utilization of quizizz applications by teaching lecturers in education management courses in the PGMI study program at IAIN Kudus. This research used a descriptive qualitative approach using the field research method with the research subjects being PGMI students in class C semester 3 at IAIN Kudus. The results of the study indicate that the utilization of quiziz applications in education management learning greatly supports students' understanding in education management courses, adds to the fun experience, and was motivated in learning, especially in education management courses. The implications of utilizing the quizizz application include: 1) Increasing Student Involvement, 2) Increased Understanding of Material, 3) Increasing Information Retention, 4) Stimulation of Student Creativity, 5) Increased Learning Motivation, 6) Efficiency of Time and Resources, 7) Increased Use of Technology in Learning, 8) More Effective Formative Assessment, 9) Increased Teacher-Student Interaction. The utilization of this game-based quzizz application greatly supports learning for both lecturers and students, and this is an attraction in the management of learning media effectively in the scope of higher education, especially at the IAIN Kudus campus, and becomes a motivation for renewal in the world of education to use learning media more effectively and creatively for the next period